Frankenstein: 200 years of graphic depiction - Ximenes, Alice (2020)
Inspired by the bicentennial anniversary of Frankenstein, or the Modern Prometheus (1818), by Mary Shelley, this is a visual research that analyses the visual representation of characters of one of the most iconic stories in popular culture. This investigation approaches two recurring themes in the graphic representation of this classic story that are still relevant in modern days. The first approach takes into consideration a speciesist interpretation of Shelley’s novel and applies it to the graphic evolution of the infamous monster, in this dissertation referred to as the creature. With the support of an academic work analysing the speciesist thinking present in Frankenstein along with a combination of references and methodologies, this approach analyses visual data from the past two hundred years ranging from book cover designs, to theatre playbills, film posters, political cartoons and other media. The second approach takes a look into the graphic evolution of the female representation in Frankenstein. Once again, supported by a combination of references and methodologies, this approach investigates the role women played in the history of Frankenstein adaptations in a diverse set of media. Although there has been extensive investigative work about Frankenstein in literature as well as different celebratory events for the bicentennial anniversary, little has been done in terms of focusing on the visual aspect of this classic tale. This fact paved the way to explore the incredibly rich graphic legacy of Frankenstein as a celebratory piece of work.